2017
DOI: 10.1103/physrevlett.119.188102
|View full text |Cite
|
Sign up to set email alerts
|

RNA Base Pairing Determines the Conformations of RNA Inside Spherical Viruses

Abstract: Many simple RNA viruses enclose their genetic material by a protein shell called the capsid. While the capsid structures are well characterized for most viruses, the structure of RNA inside the shells and the factors contributing to it remain poorly understood. We study the impact of base pairing on the conformations of RNA and find that it undergoes a swollen coil to globule continuous transition as a function of the strength of the pairing interaction. We also observe a first order transition and kink profil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…The simulations and analytical studies performed in Refs. [32][33][34][35]56] are consistent with these results: the viral RNA with a larger degree of branching has a competitive edge over the other viral RNAs or non-viral randomly branched RNAs, keeping all other chain quantities equal. Indeed, all mean-field theories, numerical calculations and simulations up to now have indicated that the encapsidation free energy of both annealed and quenched branched polymers is significantly lower than that of linear polymers.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The simulations and analytical studies performed in Refs. [32][33][34][35]56] are consistent with these results: the viral RNA with a larger degree of branching has a competitive edge over the other viral RNAs or non-viral randomly branched RNAs, keeping all other chain quantities equal. Indeed, all mean-field theories, numerical calculations and simulations up to now have indicated that the encapsidation free energy of both annealed and quenched branched polymers is significantly lower than that of linear polymers.…”
Section: Discussionsupporting
confidence: 76%
“…While previous theoretical studies have focused on the scaling behavior of linear and branched flexible polymers [32,34,35,48,[56][57][58], in this paper we study the impact of the stiffness or Kuhn length on the encapsidation of RNA by capsid proteins. In general the duplexed segments of viral RNA contain on average about five to six base-pairs [11].…”
Section: Discussionmentioning
confidence: 99%
“…Since the self-assembly of virus particles involves a wide range of thermodynamics parameters, different time scales and an extraordinary number of possible pathways, the kinetics of assembly has remained elusive, linked to Levinthal's paradox for protein folding [8,[22][23][24]. The role of the genome on the assembly pathways and the structure of the capsid is even more intriguing [5,[25][26][27][28][29][30]. The kinetics of virus growth in the presence of RNA is at least 3 orders of magnitude faster than that of empty capsid assembly, indicating that the mechanism of assembly of CPs around RNA might be quite different.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of virus assembly in the presence of genomic RNA is the need for genome compaction [ 10 ], and several groups have made important contributions to the modelling of this aspect of virus assembly [ 11 • , 12 , 13 • , 14 • ]. The impact of non-specific electrostatic interactions between genomic RNAs and CP [ 15 , 16 , 17 , 18 , 19 •• ] and of the stiffness of the RNA molecule on the assembly process [ 20 • ] have been analysed. It has also been shown that the secondary structure of the RNA molecules play an essential role in determining capsid morphology in the self-assembly of Cowpea Chlorotic Mottle Virus (CCMV)-like particles [ 21 ].…”
Section: Introductionmentioning
confidence: 99%